Water desalination by forward (direct) osmosis phenomenon: A comprehensive review - Qasim, Muhammad (2015)
Forward osmosis (FO) is a developing technology, which is thought to have a potential of producing potable water in an energy-efficient manner. FO is driven by the natural osmotic pressure difference across a semi-permeable membrane. Despite a number of patents and peer-reviewed papers published for different methods and systems for water desalination by FO, this technology is still in its infancy because of some serious limitations and challenges. Due to many environment and energy related challenges, FO-based desalination has recently gained worldwide attention because it operates at low levels of pressure and temperature. Compared to traditional pressure-driven membrane processes, FO offers recognized advantages including reversible membrane fouling, and potentially less operation energy. The purpose of this review paper is to provide the state-of-the-art of the physical principles, recent developments, and applications of forward osmosis in the area of water desalination. Strengths and limitations of the applications of FO processes in the area of water desalination are highlighted and the future of FO technology is considered.